BRAND AWARENESS ATTRIBUTES AND CUSTOMER REPEAT PATRONAGE OF SELECTED FAST FOOD ESTABLISHMENTS IN RIVERS STATE, NIGERIA - Uboegbulam, Gideon Chukwunwem (American Journals, 2023)
The primary aim of this study was to establish a relationship between brand awareness and repeat patronage of selected fast food establishments in Rivers state. The study adopted the correlational research design of quasi-experimental and Convenience sampling was chosen based on the easy-access issues for researchers in gaining information from respondents. Structured questionnaire was used as an instrument where 120 respondents from the selected fast food establishments became the unit of analysis of the study. The data collection was analyzed by using Peasrson’s product moment correlation with the aid of Package for Social Science (SPSS) version 20.0. The findings of the study revealed that there is a significant relationship between brand recognition, brand recall and customer repeat patronage. The study there recommended that managers or owners of fast food outlets must be intentional in developing awareness programs or strategies that matches the sophistication of the patrons and also managers should seek proper research on how best to penetrate the consciousness of its patrons
Keywords: Brand Awareness, Brand Recognition, Brand Recall, Purchaser Loyalty, Customer Repeat Patronage